ADSORPSI TEMBAGA(II) MENGGUNAKAN BIOMASSA Azolla microphylla DIESTERIFIKASI DENGAN ASAM SITRAT - Yunita, Tatik; Purwonugroho, Danar; Khunur, Mohammad Misbah (Jurnal Ilmu Kimia Universitas Brawijaya, 2013)
The research about adsorption of copper(II) using Azolla microphylla biomass esterified with citric acid has been conducted. The aim of this research was to determine the optimum conditions of copper(II) adsorption by Azolla microphylla biomass esterified with citric acid and adsorption capacity of esterified biomass toward copper(II). Esterification of biomass was conducted by suspending 5 g of biomass in 50 mL of 0.8 M citric acid solution followed by drying the suspension in the oven at 60 oC. Then, the dried suspension was heated at 120 oC for 3.5 hours. Batch experiments were carried out using dry biomass of 120-150 mesh at various pH of 3; 4; 5; and 6, various contact time of 30; 45; 60; 75; 90; and 120 minutes, and various copper(II) concentration of 50; 75; 100; 125; 150 mg/L. The results showed that the optimum conditions for the adsorption of copper(II) by biomass Azolla microphylla esterified with citric acid occurred at pH 5 and contact time 60 minutes. According to the Langmuir adsorption isotherm equation, it was found that the adsorption capacity (Qmax) of esterified biomass (15.625 mg/g) was smaller than that of non-esterified biomass (24.390 mg/g). Keywords: Azolla microphylla, biosorption, citric acid, copper(II), esterification.